Redetermination of the skeleton of the Asian rhinoceros in the Zoological Museum of the University Federico II, Naples (Italy) - Improta, Roberta; De Francesco, Tommaso (BORNH Bulletin of Regional Natural History, 2022)
An Asian rhinoceros skeleton is preserved in the Zoological Museum of the University Federico II of Naples (Italy). The study of the diagnostic characters of the skull has allowed to identify it as Javan rhinoceros, Rhinoceros sondaicus Desmarest, 1822. This specimen is one of the only two skeletons of Javan rhinoceros housed in Italian museums of natural history. This study also provides further morphometric data of the skull.